Oral Iron Therapy for Heart Failure With Reduced Ejection Fraction: Design and Rationale for Oral Iron Repletion Effects on Oxygen Uptake in Heart Failure. (May 2016) - Lewis, Gregory D.; Semigran, Marc J.; Givertz, Michael M.; Malhotra, Rajeev; Anstrom, Kevin J.; Hernandez, Adrian F.; Shah, Monica R.; Braunwald, Eugene
Abstract : N/A: Iron deficiency is present in ≈50% of patients with heart failure and is an independent predictor of mortality. Despite growing recognition of the functional and prognostic significance of iron deficiency, randomized multicenter trials exploring the use of oral iron supplementation in heart failure, a therapy that is inexpensive, readily available, and safe, have not been performed. Moreover, patient characteristics that influence responsiveness to oral iron in patients with heart failure have not been defined. Although results of intravenous iron repletion trials have been promising, regularly treating patients with intravenous iron products is both expensive and poses logistical challenges for outpatients. Herein, we describe the rationale for the Oral Iron Repletion effects on Oxygen Uptake in Heart Failure (IRONOUT HF) trial. This National Institute of Health-sponsored trial will investigate oral iron polysaccharide compared with matching placebo with the primary end point of change in exercise capacity as measured by peak oxygen consumption at baseline and at 16 weeks. Clinical Trial Registration—: URL:http://www.clinicaltrials.gov . Unique identifier: NCT02188784. Abstract : Supplemental Digital Content is available in the text.